The δ-thermostat: Selective normal-modes excitation by colored-noise Langevin dynamics - Ceriotti, M; Parrinello, M (2010)
Recently, the authors introduced a comprehensive framework to use a custom-tailored Langevin equation with correlated-noise in the context of molecular-dynamics simulations. Here it is established how such a framework can be used to selectively excite normal modes whose frequency falls within a prescribed, narrow range. Possible application of this technique to the diagonalization of large matrices is also discussed. © 2010 Published by Elsevier Ltd.